Calçando as sandálias de professora/artista/pesquisadora: reflexões, diálogos e práticas narrativas - Nascimento, Aline Barbosa (2016)
This narrative and autobiographical nature research addresses the formative processes of a theater teacher / artist / researcher and her initiation into the practice of teaching. It describes the steps taken and the experiences accumulated over the life course, from basic education to vocational training, with an emphasis on the teaching practice in a public elementary school education in São Luís (MA). The memory taken up work led to the construction of a retrospective look at the rethinking of education, artistic practice and teaching, inspiring reflections on events, conditions and subjectivities leading up to and at the same time staked out an investigative process developed for the professional master's degree in Education of Arts. From the participant observation of a school theater group - Behind the scenes, the UEB Prof. Sa Valle - involving documentation of rehearsals and registration of images, among others, and a dialogue with the literature, the focus turns narrative to attempt to contribute to the knowledge on the formation of theater teachers, giving emphasis on artistic production and research on creative behavior.